Catalanophobia: una qüestió d’Estat - Marfull Pujadas, Andreu (Ediciones de La Tempestad SL, 2018)
http://ccuc.cbuc.cat/search~S23?/aMarfull%2C+Andreu/amarfull+andreu/-3%2C0%2C0%2CB/frameset&FF=amarfull+i+pujadas+andreu+++++1971&1%2C%2C6/indexsort=-